Some thoughts on biolinguistics - Boeckx, Cedrix (Veritas (Porto Alegre), 2015)
Naïve depictions of the biology of language are unable to treat the real complexity observed by biologists at all levels of analysis, and consequently they do not bring us closer to an accurate depiction of the nature of human language and the human mind. The aim of this essay is to show that if a real biolinguistics is intended to be achieved we ought to be compelled to go beyond these depictions.